Dampak Pelaksanaan Pemekaran Kecamatan dalam Meningkatkan Pembangunan Daerah - Maryam D. Poma; I Kadek Satria Arsana; Iin Laki; Ansar Sahabi (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2021)
Regional expansion aims to increase development evenly. Bulango Ulu is a new sub-district which is a division of North Bulango District. This study aims to determine the impact of sub-district expansion in increasing development in Bulango Ulu District. This research uses a qualitative descriptive research type. The focus in this research is communication, attitude, and natural resource management. In this study, data were obtained from primary data and secondary data through observation, interviews, and documentation techniques. The results of the study indicate that communication between the sub-district government and the district government is a one-way communication and there has been no serious feedback or response from the government. The Government of Bone Bolango Regency has not given attention or solutions because the required budget is quite large in providing adequate infrastructure. The attitude of the apparatus in providing services to the community is good. However, there are some officers who are less friendly when serving the community. The ability of the community to manage natural resources in Bulango Ulu District is not optimal. Infrastructure development in Bulango Ulu District is running slowly. Therefore, the impact of the division of sub-districts in increasing development has not been optimal even though it has been 14 (fourteen) years of division. Pemekaran daerah bertujuan untuk meningkatkan pembangunan secara merata. Bulango Ulu merupakan kecamatan baru hasil pemekaran dari Kecamatan Bulango Utara. Penelitian ini bertujuan untuk mengetahui dampak pemekaran kecamatan dalam peningkatan pembangunan di Kecamatan Bulango Ulu. Pada penelitian ini menggunakan jenis penelitian deskriptif kualitatif. Fokus dalam penelitian ini adalah komunikasi, sikap, dan pengelolaan sumber daya alam. Data diperoleh dari data primer dan data sekunder melalui teknik observasi, wawancara, serta dokumentasi. Hasil penelitian menunjukkan bahwa komunikasi antara pemerintah kecamatan dengan pemerintah kabupaten merupakan komunikasi searah dan belum ada feedback ataupun respon yang serius dari pemerintah. Pemerintah Kabupaten Bone Bolango belum memberikan perhatian maupun solusi sebab anggaran yang dibutuhkan cukup besar dalam menyediakan infrastruktur yang memadai. Sikap aparat dalam pemberian pelayanan kepada masyarakat sudah baik. Namun ada beberapa aparat yang kurang ramah ketika melayani masyarakat. Kemampuan masyarakat untuk mengelola sumber daya alam di Kecamatan Bulango Ulu belum optimal. Pembangunan infrastruktur di Kecamatan Bulango Ulu tergolong berjalan dengan lamban. Oleh karena itu, dampak pemekaran kecamatan dalam meningkatkan pembangunan belum berjalan optimal meskipun sudah 14 (empat belas) tahun dimekarkan.